Model Kompetensi Pengajaran dan Pembelajaran (PdP) dan Pengukuhan Program Engineer Huffaz di Universiti Malaysia Pahang - Rashidi, Abbas (Centre for Modern Languages & Human Sciences, UMP, 2018)
This study aims to investigate and analyse Huffaz engineering programme teaching and learning (T&L), and enhancement competency model at Universiti Malaysia Pahang. The study involved 20 respondents who were from Bachelor Degree in Mechanical, Electrical, Computer Science and Chemical Engineering. The research design included the inductive-deductive technique to produce enhancement and competency model for Huffaz engineering programme, as well as the design and developmental research approach by Ritchey dan Klien (2007). Findings showed the enhancement model for Huffaz engineering was developed in three models (Huffaz-M (3M)) namely through memorisation, reiteration (Murajaah) and remembrance (Muzakarah). Through the Huffaz-M model, the students’ competency model in teaching and learning (T&L) Huffaz engineering programme was developed i.e. 1Q2T: recitation (Qiraah), understanding (Tilawah) and memorisation (Tahfiz). 1Q2T model is anticipated to aid the country’s aspiration in its aim to proliferate 125, 000 professional Huffaz by 2025.